Efficacy of hyperbaric oxygen therapy as an adjunct therapy in the treatment of sleep disorders among patients with Parkinson’s disease: a meta-analysis - Tan, Wei-qiang; Liu, Qing; Cen, Ming-jun; Leong, Ian I.; Pan, Zhao-quan; Liao, Mu-xi; Zhuang, Li-xing (Frontiers in Neurology, 2024)
Objective To systematically evaluate the efficacy of hyperbaric oxygen therapy (HBOT) as an adjunct therapy for treating sleep disorders in patients with Parkinson’s disease (PD). Methods We conducted comprehensive searches in eight databases from inception through September 2023, including PubMed, Cochrane Library, Embase, Web of Science, SinoMed, China National Knowledge Infrastructure (CNKI), China Science and Technology Periodical Database (VIP), and Wanfang Database. The objective was to identify randomized controlled trials (RCTs) evaluating HBOT’s effectiveness in alleviating sleep disorder symptoms in PD patients as an adjunct therapy. Literature screening and data extraction were independently executed by the authors. Meta-analyses were performed using Review Manager 5.3 software, and publication bias and sensitivity analyses were assessed using Stata 17.0 software. Results Seven RCTs involving 461 participants were included. The findings revealed that the addition of HBOT significantly enhanced sleep efficiency (MD = 15.26, 95% CI [10.89, 19.63], p < 0.00001), increased time in bed (MD = 69.65, 95% CI [43.01, 96.30], p < 0.00001), total sleep time (MD = 75.87, 95% CI [25.42, 126.31], p = 0.003), slow-wave sleep (SWS) time (MD = 6.14, 95% CI [3.95, 8.34], p < 0.00001), and rapid eye movement sleep (REM) time (MD = 4.07, 95% CI [2.05, 6.08], p < 0.0001), and reduced awakening frequency (MD = −11.55, 95% CI [−15.42, −7.68], p < 0.00001) and sleep latency (MD = −6.60, 95% CI [−9.43, −3.89], p < 0.00001). Additionally, significant improvements were observed in the Pittsburgh Sleep Quality Index (PSQI) (MD = −2.52, 95% CI [−2.85, −2.18], p < 0.00001), Epworth Sleepiness Scale (ESS) (MD = −2.90, 95% CI [−3.34, −2.47], p < 0.00001), Unified Parkinson’s Disease Rating Scale Part III (UPDRS III) (MD = −1.32, 95% CI [−2.16, −0.47], p = 0.002), and Hoehn and Yahr grading (H-Y grading) (MD = −0.15, 95% CI [−0.28, −0.01], p = 0.03). Conclusion The current meta-analysis supports the efficacy of HBOT as an adjunct therapy in managing sleep disorders in PD patients. It is recommended for PD patients experiencing sleep disturbances. Systematic review registration:https://www.crd.york.ac.uk/, identifier: CRD42023462201.